Election Security and Economics: It's All About Eve - David Basin; Hans Gersbach; Akaki Mamageishvili; Lara Schmid; Oriol Tejada (ETH Zurich, CER-ETH - Center of Economic Research, 2017)
A system's security must be understood with respect to the capabilities and be- haviors of an adversary Eve. It is often assumed in security analysis that Eve acts as ma- liciously as possible. From an economic perspective, Eve tries to maximize her utility in a game with other participants. The game's rules are determined by the system and its security mechanisms, but Eve can invent new ways of interacting with participants. We show that Eve can be used as an interface to explore the interplay between security and economics in the domain of elections. Through examples, we illustrate how reasoning from both disciplines may be combined to explicate Eve's motives and capabilities and how this analysis could be used for reasoning about the security and performance of elections. We also point to future research directions at the intersection of these disciplines.
Keywords: A11; A12; D70; 330; Voting; E-Voting; Security